Characterization of aggresome formation in choroid plexus carcinoma. - Nassar, Marwa Mohamed Ali (AUC Knowledge Fountain, 2017)
Protein misfolding is inevitable, 30% of newly synthesized polypeptides can end up misfolded, and such proteins are either refolded or eliminated by cellular quality control pathways. These pathways include the ubiquitin proteosome system and autophagy. In recent years, protein misfolding has been implicated in the pathophysiology of many diseases such as diabetes, neurological disorders and cancer. Studies from our laboratory have shown that choroid plexus carcinoma tumors are characterized by the formation of aggresomes at the microtubules organizing centers (MTOC) in formalin fixed and paraffin embedded (FFPE) tumor tissues. This was further confirmed by the development of choroid plexus carcinoma cell line (CCHE-45) which was characterized by the constitutive formation of aggresomes at MTOC. Aggresome formation implies presence of toxic protein over load and/or defective autophagy. The role of autophagic flux in the removal of aggresomes was further investigated. CCHE-45 cells displayed an increase in both basal and induced autophagic flux. Furthermore, microtubule-associated protein light chain 3 A- variant 1 (LC3A-V1) expression was silenced by promoter methylation in these cells. Restoring LC3A-V1 resulted in the elimination of the aggresomes and the recruitment of Lysosomal-Associated Membrane Protein (LAMP2) independent from autophagosome formation. Based on these findings we suggest that quality control autophagy in CCHE-45 is mediated by LC3A in aggresomes clearance. We propose that perturbation in the autophagic pathway by the absence of LC3A expression leads to a failure in aggresome degradation thus overcoming misfolded protein overload.